Nutrigenomics and proteomics in health and disease : towards a systems-level understanding of gene-diet interactions - Kussmann, Martin; Stover, Patrick J. (Functional food science and technology, 2017)
"This volume brings together leading experts in the areas of nutrition, nutrigenomics, metabolic programming, food-based bioactive dietary components and the gut microbiome, as well as those expert in the application of innovative tools and methods for statistical and biological network analysis, which are now at the forefront of nutritional and biomedical sciences. The articles provide a roadmap for the integration of normative science methods and approaches with more comprehensive systems biology-based investigations that deploy a multitude of omic platforms. This integration is essential to escape the bottleneck in knowledge generation by applying decades of knowledge of nutrients and their function to comprehensive omics and clinical data acquisition, processing, visualization, and interpretation. Achieving a systems-level understanding of nutrient function in health and disease will usher in an age of precision nutrition in support of maximizing human health and potential"--